Comparing Different Methods to Detect and Correct Nonresponse Bias in Postal Questionnaire Studies - Martin Tickle, PhD; Keith M. Milsom, MSc; Tony M. Jenner, MSc; Anthony S. Blinkhorn, PhD (Blackwell Synergy, 2003)
This study compares methods for detecting and correcting the bias associated with nonresponse to postal questionnaires